The accident ebook - Pavone, Chris (2014)
From the author of the New York Times -bestselling and Edgar Award-winning The Expats   As dawn approaches in New York, literary agent Isabel Reed is turning the final pages of a mysterious, anonymous manuscript, racing through the explosive revelations about powerful people, as well as long-hidden secrets about her own past. In Copenhagen, veteran CIA operative Hayden Gray, determined that this sweeping story be buried, is suddenly staring down the barrel of an unexpected gun. And in Zurich, the author himself is hiding in a shadowy expat life, trying to atone for a lifetime’s worth of lies and betrayals with publication of The Accident, while always looking over his shoulder. Over the course of one long, desperate, increasingly perilous day, these lives collide as the book begins its dangerous march toward publication, toward saving or ruining careers and companies, placing everything at risk—and everyone in mortal peril.  The rich cast of characters—in publishing and film, politics and espionage—are all forced to confront the consequences of their ambitions, the schisms between their ideal selves and the people they actually became. The action rockets around Europe and across America, with an intricate web of duplicities stretching back a quarter-century to a dark winding road in upstate New York, where the shocking truth about the accident itself is buried. Gripping, sophisticated, layered, and impossible to put down, The Accident proves once again that Chris Pavone is a true master of suspense.